"Forever young"—Postnatal growth inhibition of the turbinal skeleton in brachycephalic dog breeds (Canis lupus familiaris). Issue 1 (28th May 2020) - Wagner, Franziska; Ruf, Irina
Abstract: In short snouted (brachycephalic) dogs ( Canis lupus familiaris ), several genetic mutations cause postnatal growth inhibition of the viscerocranium. Thus, for example, the pug keeps a snub nose like that observed in neonate dogs in general. However, little is known how far intranasal structures like the turbinal skeleton are also affected. In the present study, we provide the first detailed morphological and morphometric analyses on the turbinal skeleton of pug, Japanese chin, pekingese, King Charles spaniel, and Cavalier. In order to elucidate how a shortened snout affects turbinal shape, size, and density, our sample covers different degrees of brachycephaly. Macerated skulls of 1 juvenile and 17 adult individuals were investigated by μCT and virtual 3D reconstructions. In addition, histological serial sections of two prenatal and one neonate whippet were taken into account. All investigated postnatal stages show three frontoturbinals and three ethmoturbinals similar to longer snouted breeds, whereas the number of interturbinals is reduced. The shape of the entire turbinal skeleton simplifies with decreasing snout length, that is, within a minimized nasal cavity the turbinals decrease proportionally in surface area and surface density due to a looser arrangement. We interpret these apparent reductions as a result of spatial constraint which affects postnatal appositional bone growth and the position of the turbinals inside the nasal cavity. The turbinal skeleton of brachycephalic dogs arrests at an early ontogenetic stage, corresponding with previous studies on the dermal bones. Hence, we assume an association between the growth of intranasal structures and facial elongation.